Market screening model - Kho, Soo Pei (2014)
It is crucial for a company to have a systematic market screening process to help it make correct market entry decisions. Hence, the group has developed a comprehensive market screening model that incorporates various models that have been developed by other authors. This model may serve as a useful guide to Singapore companies who are considering venturing overseas.